A kinematic analysis of the jumping front-leg axe-kick in taekwondo - Preuschl, E.; Hassmann, M.; Baca, A. (Journal of Sports Science & Medicine, 2016)
The jumping front-leg axe-kick is a valid attacking and counterattacking technique in Taekwondo competition (Streif, 1993). Yet, the existing literature on this technique is sparse (Kloiber et al., 2009). Therefore, the goal of this study was to determine parameters contributing significantly to maximum linear speed of the foot at impact. Parameters are timing of segment and joint angular velocity characteristics and segment lengths of the kicking leg. Moreover, we were interested in the prevalence of proximal-to-distal-sequencing. Three-dimensional kinematics of the kicks of 22 male Taekwondo-athletes (age: 23.3 ± 5.3 years) were recorded via a motion capturing system (Vicon Motion Systems Limited, Oxford, UK). The participants performed maximum effort kicks onto a rack-held kicking pad. Only the kick with the highest impact velocity was analysed, as it was assumed to represent the individual`s best performance. Significant Pearson correlations to impact velocity were found for pelvis tilt angular displacement (r = 0.468, p < 0.05) and for hip extension angular velocity (r = -0.446, p < 0.05) and for the timing of the minima of pelvis tilt velocity (r = -0.426, p < 0.05) and knee flexion velocity (r = -0.480, p < 0.05). Backward step linear regression analysis suggests a model consisting of three predictor variables: pelvis tilt angular displacement, hip flexion velocity at target contact and timing of pelvic tilt angular velocity minimum (adjusted R2 = 0.524). Results of Chi-Squared tests show that neither for the leg-raising period (?2 = 2.909) of the technique, nor for the leg-lowering period a pattern of proximal-to-distal sequencing is prevalent (?2 = 0.727). From the results we conclude that the jumping front-leg axe-kick does not follow a proximal-to-distal pattern. Raising the leg early in the technique and apprehending the upper body to be leant back during the leg-lowering period seems to be beneficial for high impact velocity. Furthermore, striking by extending the hip rather than by flexing the knee could raise impact velocity.